2001
DOI: 10.1159/000054022
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Deters the Outgrowth of Serotonergic Neurons at Midgestation

Abstract: We have previously demonstrated that treatment of pregnant C57BL mice from gestation days 8 to 14 with alcohol with 20% ethanol-derived calories (EDC) reduced the number of serotonin (5-HT) neurons and retarded their migration in the fetal brains. In the present study, we obtained similar results with the use of 25% EDC and extended our previous findings by demonstrating that besides the alteration of the number of 5-HT neurons, prenatal alcohol exposure also affects their projecting fibers in their early deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 29 publications
1
20
0
Order By: Relevance
“…Webster and colleagues suggested that during the period between E7 to E13 and also later ages, the developing brain exhibited the highest susceptibility to alcohol exposure. Moreover, using similar drinking paradigm (25% EDC), we have shown that prenatal alcohol exposure from E7 to E13, E15 and/or E18 caused brain growth deficits, reduction in the size of fetal brain regions and reduction in the number of serotonin neurons (Sari et al, 2001, Sari and Zhou, 2004, Sari and Gozes, 2006, Sari, 2009). …”
Section: Discussionmentioning
confidence: 89%
“…Webster and colleagues suggested that during the period between E7 to E13 and also later ages, the developing brain exhibited the highest susceptibility to alcohol exposure. Moreover, using similar drinking paradigm (25% EDC), we have shown that prenatal alcohol exposure from E7 to E13, E15 and/or E18 caused brain growth deficits, reduction in the size of fetal brain regions and reduction in the number of serotonin neurons (Sari et al, 2001, Sari and Zhou, 2004, Sari and Gozes, 2006, Sari, 2009). …”
Section: Discussionmentioning
confidence: 89%
“…Prenatal exposure to alcohol in the maternal circulation is also associated with reduced 5-HT receptor binding (Fig 4) (Kinney et al 2003). In animal models of prenatal alcohol exposure, various abnormalities of the 5-HT system have been observed, including reduced 5-HT levels and reduced 5-HT receptor binding (Druse et al 1988), retarded process outgrowth and migration of 5-HT neurons, reduced density of 5-HT fibers in the medial forebrain bundle, and reduced 5-HT neurons in the median and dorsal raphé (Sari et al 2001; Zhou et al 2002) and lower brainstem (Druse et al 2004). Prenatal alcohol also adversely affects signaling molecules and transcription factors necessary for 5-HT development, e.g., sonic hedgehog which is involved in the early specification of 5-HT precursors (Ahlgren et al 1999; Ahlgren et al 2002), and results in defective neurogenesis, cell migration, synaptogenesis, and dendritic organization (Haydon et al 1987; Lauder 1990; Ivgy-May et al 1994; Mazer et al 1997; Werner et al 1998; Faber et al 1999; Luo et al 2003; Kondoh et al 2004).…”
Section: Medullary 5-ht System Abnormalities In Sids Originate Durmentioning
confidence: 99%
“…The neurotoxic effects of ethanol may also cause disruptions in the development of neurotransmitter systems, such as the serotonin, dopamine, gamma‐aminobutyric acid (GABA), glutamate and norepinephrine systems at prenatal or postnatal stages in rodents and non‐human primates (Druse et al, 1991; Maier et al, 1996; Miller, 2006; Sari and Gozes, 2006; Sari et al, 2001; Sari and Zhou, 2004; Tajuddin and Druse, 1999; Zhou et al, 2002). Serotonin is one of the first neurotransmitter systems to develop during ontogeny; it forms before the genesis of most other transmitter neurons.…”
Section: Introductionmentioning
confidence: 99%
“…Prenatal alcohol exposure lowers serotonin uptake in rats at a mid‐gestation stage (Druse et al, 1991, 2004; Tajuddin and Druse, 1999). We previously found that prenatal alcohol exposure from embryonic day 7 (E7) to E15–18 reduces the number of serotonin neurons and the density of serotonin‐immunoreactive fibers in several fetal brain regions (Sari and Gozes, 2006; Sari et al, 2001; Sari and Zhou, 2004; Zhou et al, 2002, 2005). HPLC assays from a previous study demonstrated that prenatal alcohol exposure reduces the levels of dopamine and serotonin while increasing the levels of GABA in E20 fetal brains (Maier et al, 1996).…”
Section: Introductionmentioning
confidence: 99%